Estimasi Parameter Regresi Linear Pada Kasus Data Outlier Menggunakan Metode Estimasi Method Of Moment - Hisyam Ihsan; Wahidah Sanusi; Nurfadillah (Journal of Mathematics, Computations and Statistics, 2018)
This research examined one of a robust regression method which was Moment of Moment estimation method. Robust regression is a regression method used when there is an outlier on the model. The purpose of this research was to determine the model of robust regression equation using Method of Moment estimation method. Before estimating the parameters by Method of Moment method, firstly the data was identified using the DfFITS to determine whether the data contains an outlier. After the data was analyzed and the outlier was detected, the researcher estimated the parameter using Method of Moment estimation method to get the regression model that was not affected by the outlier data. Based on the analysis result, the equation of regression model of Method of Moment estimation method was Y = -34305 + 5 X1 + 634 X2 with the value of R 2 = 0.923. Thus, the effect of harvested area and productivity on the amount of corn production was 92.3% while the rest was affected by other variables.